2015
DOI: 10.1111/bph.13156
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol dilates mesenteric arteries and reduces systemic BP by activating endothelial cell TRPV4 channels

Abstract: BACKGROUND AND PURPOSEEugenol, a vanilloid molecule found in some dietary plants, relaxes vasculature in part via an endothelium-dependent process; however, the mechanisms involved are unclear. Here, we investigated the endothelial cell-mediated mechanism by which eugenol modulates rat mesenteric artery contractility and systemic BP. EXPERIMENTAL APPROACHThe isometric tension of rat mesenteric arteries (size 200-300 μm) was measured using wire myography; non-selective cation currents (ICat) were recorded in en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 66 publications
1
37
0
Order By: Relevance
“…To explain the observed significant dependence of 4αPDD-induced relaxation on stimulation of endothelial TRPV4 channels, immunohistochemical analysis was employed and it revealed that TRPV4 channels are mainly expressed on the endothelium of mesenteric arteries in both WKY and SHR, and in agreement with previous studies on mouse mesenteric and aortic arteries (Zhang et al 2009, Mendoza et al 2010, and rat mesenteric, pulmonary and carotid arteries (Loot et al 2008, Willette et al 2008, Sukumaran et al 2013, Peixoto-Neves et al 2015. Furthermore, the immunofluorescent signal for TRPV4 protein that was seen in the endothelial cells of wild-type mesenteric and carotid arteries was not seen in those of TRPV4 -/mice (Hartmannsgruber et al 2007, Mendoza et al 2010).…”
Section: Discussionsupporting
confidence: 83%
“…To explain the observed significant dependence of 4αPDD-induced relaxation on stimulation of endothelial TRPV4 channels, immunohistochemical analysis was employed and it revealed that TRPV4 channels are mainly expressed on the endothelium of mesenteric arteries in both WKY and SHR, and in agreement with previous studies on mouse mesenteric and aortic arteries (Zhang et al 2009, Mendoza et al 2010, and rat mesenteric, pulmonary and carotid arteries (Loot et al 2008, Willette et al 2008, Sukumaran et al 2013, Peixoto-Neves et al 2015. Furthermore, the immunofluorescent signal for TRPV4 protein that was seen in the endothelial cells of wild-type mesenteric and carotid arteries was not seen in those of TRPV4 -/mice (Hartmannsgruber et al 2007, Mendoza et al 2010).…”
Section: Discussionsupporting
confidence: 83%
“…An alternative pathway is that increased intracellular calcium in vascular endothelial cells activates NOS and subsequent vasodilation through NO‐related mechanism . This idea is based on a previous study showing that L‐NAME, an NOS inhibitor, blocked TRPV4‐mediated vasodilation in mesenteric arteries . However, this mechanism is unlikely because chronic hypoperfusion did not affect vasoconstriction of PAs to NOS inhibitor L‐NNA, suggesting NO production was not increased after UCCAo.…”
Section: Discussionmentioning
confidence: 99%
“…, see section ), also cause relaxations which are partly endothelium‐dependent (with both NO and EDH contributing) and are due to the opening of endothelial TRPV4 channels (Peixoto‐Neves et al . ), while their endothelium‐independent vasodilator properties result from inhibition of L‐type Ca 2+ channels in vascular smooth muscle (Raffai et al . ).…”
Section: Nitric Oxidementioning
confidence: 99%